PL5. Training and education in Europe, Middle East, Africa, Latin America and Asia Oceania chapters, IFCN: An international survey. Issue 8 (August 2021) - Cole, Jonathan
Abstract : The chapters of the IFCN, Asia Oceania (AOC), Europe Middle East and Africa, (EMEAC), Latin America (LAC), and North America (NAC), have cooperated to undertake, for the first time, a survey of training and education practice in their national societies. The results have been pooled so that data on aspects of our practice may now be compared and contrasted. The survey looked at the status of clinical neurophysiology, (mono- or subspecialty) within countries, training duration, numbers of cases seen independently for competence, examination methods, the presence of a national curriculum and who controls it, how competency was examined, and accreditation. It also considered training for technicians, clinical practice including waits and methods of funding, revalidation and, lastly, concerns within our specialty. Clinical Neurophysiology remains a monospecialty in 16 out of 59 countries. Training durations vary between 1 and 5 years, with most lasting 2–3 years in the LAC and AOC, whilst in the EMAEC there is a fairly even spread of durations between the 1 to 5 years. An exit exam is present in 50% EMEAC societies, 75% of AOC and in 3 out for 12 LAC ones. The numbers of EMG and EEG tests performed necessary for competence were <250 to >750. In the EMEAC, half the societies required over 500 EMG and EEG tests, whilst the AOC required fewer. Technicians were usually trained for 2–4 years. Within the EMEAC there is no formal requirement for continuing education or for revalidation in 64%. In the AOC, continuing medical education is required in 11 out of 12 countries, but revalidation needed only in 4. The main concerns were over workload in EMEAC and in the provision of training in AOC. Work has also been taking place in a draft curriculum. The utility of these initiatives remains to be determined, but at least, for the first time, some comparative data on training and education around the world is being assembled.